Systematic Literature Review (SLR): Curriculum 4.0: Integrating Technology in Learning to Improve Students’ Competence - Pujilestari, Pujilestari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Curriculum 4.0 is a response to technological advancements in the era of the Industrial Revolution 4.0, aiming to integrate technology into education to enhance student competencies. This integration involves the use of artificial intelligence, the Internet of Things, big data, and blockchain, which are expected to make education more effective, efficient, and relevant. This study uses the Systematic Literature Review (SLR) method to evaluate effective strategies for integrating technology in education. The results show that technology can support the development of 21st-century skills such as critical thinking, creativity, collaboration, and communication. However, the implementation of Curriculum 4.0 faces challenges such as the digital divide and teacher readiness. Training and professional development for teachers, as well as support from the government, industry, and community, are needed to overcome these challenges. With the right strategies, Curriculum 4.0 has the potential to improve the quality of education and prepare students to face future challenges.